2014
DOI: 10.1126/science.1256800
|View full text |Cite
|
Sign up to set email alerts
|

C9orf72 repeat expansions cause neurodegeneration in Drosophila through arginine-rich proteins

Abstract: An expanded GGGGCC repeat in C9orf72 is the most common genetic cause of frontotemporal dementia and amyotrophic lateral sclerosis. A fundamental question is whether toxicity is driven by the repeat RNA itself and/or by dipeptide repeat proteins generated by repeat-associated, non-ATG translation. To address this question we developed in vitro and in vivo models to dissect repeat RNA and dipeptide repeat protein toxicity. Expression of pure repeats in Drosophila caused adult-onset neurodegeneration attributabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

63
906
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 660 publications
(972 citation statements)
references
References 34 publications
63
906
3
Order By: Relevance
“…Furthermore, elimination of the ATG initiation codon abolished the toxic effect of the PR construct. The finding that mostly arginine-containing DPRs display neurotoxicity in this in vivo model is in line with the findings in Drosophila [4,33] and provides evidence for a potential role of these DPRs in C9 ALS/FTD pathology. Despite the observation of GA forming abundant aggregates, it failed to induce motor axon toxicity in our model.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Furthermore, elimination of the ATG initiation codon abolished the toxic effect of the PR construct. The finding that mostly arginine-containing DPRs display neurotoxicity in this in vivo model is in line with the findings in Drosophila [4,33] and provides evidence for a potential role of these DPRs in C9 ALS/FTD pathology. Despite the observation of GA forming abundant aggregates, it failed to induce motor axon toxicity in our model.…”
Section: Discussionsupporting
confidence: 76%
“…It has previously been shown that these constructs are not RAN translated and do not generate DPRs, while they still adopt the same stable conformation as the uninterrupted GGG GCC repeat RNA [33]. Interestingly, in spite of not being able to generate DPRs, sense RO repeat RNA (70RO and 108RO) still significantly affected axonal length and axonal branching, although to a somewhat lesser degree than the uninterrupted repeat RNA (Fig.…”
Section: Repeat Rna Toxicity Is Independent Of Dpr Toxicitymentioning
confidence: 95%
See 2 more Smart Citations
“…The G 4 C 2 repeat is translated in all reading frames in both the sense and antisense strands, resulting in several different dipeptides that accumulate specifically within the cells of patients carrying pathogenic (>22) repeat lengths. These dipeptides are toxic to cells in vitro and in vivo [69,[136][137][138], causing cell death in some cases by disrupting RNA processing within nucleoli [69], or by altering the function of essential proteins such as Unc119 [137], a trafficking factor required for axon development [139]. Moreover, the sequestration of RNA binding proteins by expanded G 4 C 2 RNA may be synergistic with the toxicity induced by RAN translation products [138]: many of the proteins bound by G 4 C 2 RNA catalyze the nuclear export of RNA, potentially facilitating cytoplasmic RAN translation of expanded C9orf72 repeats and accentuating toxicity [121].…”
Section: Alternative Rna-based Mechanismsmentioning
confidence: 99%